Wireless Access Flexibility First International Workshop, WiFlex 2013, Kaliningrad, Russia, September 4-6, 2013. Proceedings - Bianchi, Giuseppe; Lyakhov, Andrey; Khorov, Evgeny; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the First International Workshop on Wireless Access Flexibility, WiFlex 2013, held in Kaliningrad, Russia, in September 2013. The 13 full papers presented were carefully reviewed and selected for inclusion in this volume. The papers describe the latest results and novel research ideas in the field of flexible wireless access architecture design opening the door for innovative solutions significantly improving network performance. The following topics are covered in this volume: 4G and beyond, local area networks, multi-hop networks, sensor networks.
Delay and Loss Due to Uplink Packet Scheduling in LTE Network -- Distributed Adaptive Interference Control in 4G Small Cell Networks -- Smart Cities Software: Customized Messages for Mobile Subscribers -- 802.11 Buffers: When Bigger Is Not Better? -- On the Capacity of a PPM UWB Multiple-Access System with a Single User Noncoherent Reception -- Detecting Transmission Power Misbehaviour in Wi-Fi Networks -- P-Persistent Queue Management to Overcome Channel Failures in IEEE 802.11 Networks for Real-Time Multimedia Streaming -- Supporting a Pseudo-TDMA Access Scheme in Mesh Wireless Networks -- Dynamic Resource Allocation for MCCA-Based Streaming in Wi-Fi Mesh Networks -- Distributed Clock Synchronization Algorithm for Wide-Range TDMA Ad Hoc Networks -- Joint Integrated Spectrum Handoff Management and Routing in CR-MANETs: An Analytical Modeling -- Dimensioning Self-sufficient Networks of Energy Harvesting Embedded Devices -- Experiment Design for Parameter Estimation in Sensing Models.
Keywords: Computer science; Computer Communication Networks; Computer Science; Computer Communication Networks